154k views
4 votes
Let p=x^2+6p=x 2 +6p, equals, x, start superscript, 2, end superscript, plus, 6. Which equation is equivalent to (x^2+6)^2-21=4x^2+24(x 2 +6) 2 ?21=4x 2 +24left parenthesis, x, start superscript, 2, end superscript, plus, 6, right parenthesis, start superscript, 2, end superscript, minus, 21, equals, 4, x, start superscript, 2, end superscript, plus, 24 in terms of p ?

User S McCrohan
by
4.5k points

2 Answers

0 votes

Answer:

Explanation:

Let p=x^2+6p=x 2 +6p, equals, x, start superscript, 2, end superscript, plus, 6. Which-example-1
User PhilD
by
5.2k points
3 votes

Answer:

(p+3)(p-7) = 0

Explanation:

Given p=x^2+6p and (x^2+6)^2-21=4x^2+24

We are to substitute the the p = x²+6 into the expression as shown;

The expression (x^2+6)^2-21=4x^2+24 will become

(x²+6)²-21 = 4(x²+6)

On substituting p, the expression becomes;

p²-21 = 4p

Subtract 4p from both sides

p²-21-4p = 4p-4p

p²-4p-21 = 0

p²-7p+3p-21 = 0

p(p-7)+3(p-7) = 0

(p+3)(p-7) = 0

Hence the expression in terms of p is (p+3)(p-7) = 0

User Amalloy
by
4.3k points